(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: To demonstrate, through a demonstration of the complexity of ecosystem risks, that the criminal consequences of climate change require a specific criminological and criminal justice approach. Methodology: The thematic systematisation of new findings and conclusions produced by the co-disciplines in the scientific literature at a speed different from traditional publishing patterns. This will involve testing and applying artificial intelligence-enabled source literature retrieval techniques. Findings: The consequences of climate change are reaching the forensic sciences. It is important to define the hierarchy of damages, to establish the mutual effects of the consequences of damages, the direct and indirect consequences of damages, the present and expected future severity of the consequences suffered by direct and indirect victims. These phenomena are interlinked not only hierarchically but also in a networked way. If environmental protection is to be more effective than it is at present, moral, political and legal responsibilities need to be grouped and differentiated as described above. Value: To demonstrate that effective criminal justice action against ecocide crimes can only be achieved through a systems approach to globally manifested harms.